MODEL PEMBELAJARAN MAKE A MATCH UNTUK PEMBELAJARAN IPA YANG MENYENANGKAN - Yudi Wijanarko (Universitas Sarjanawiyata Tamansiswa, 2017)
The learning process of Natural Science subject in elementary schools is supposed to implement method, strategy and model which have many variations, so that the ongoing learning process is perceived as something fun by the students; thus, it can enhance their motivation in learning. The selection of the method, strategy and learning model are supposed to be adjusted with the materials which will be delivered in class, with the purpose that there will be no learning material which is missed and in other hand, it has a purpose to trigger the students to be active and feel it fun to learn. The learning model of â€œmake a matchâ€ is one of the learning models, which can be used in delivering natural science materials in elementary schools. It is because the learning model â€œmake a matchâ€ has characteristic that is close to studentsâ€™ characteristic that is fond of playing games. Besides, the learning materials of natural science are really close with the studentsâ€™ life so that the uses of this learning model trigger the students to be more active and make the students perceive that learning natural science subject is fun that subsequently may enhance the competence of the students themselves as it is seen in their score.